Determinants of bryophyte assemblages in traditionally managed grasslands of the Carpathian Mts. Issue 2 (8th April 2022) - Janišová, Monika; Širka, Pavel; Palpurina, Salza; Magnes, Martin; Kuzemko, Anna; Dembicz, Iwona; Kozub, Łukasz
Abstract: Questions: Although bryophytes play an important role in grassland ecosystems, environmental factors that drive bryophyte assemblages were rarely studied, especially in low‐intensity traditional grasslands. Therefore, using fine‐scale data on bryophyte assemblages in traditionally managed secondary grasslands, we studied the relative importance of several sets of environmental drivers (related to topography, soil properties, landscape, and management) of: (i) taxonomic and functional compositions; and (ii) cover and species richness of bryophyte communities. Location: Central and Eastern Europe, Carpathian Mountains, 15 sites with preserved traditional management practices distributed in Romania (six sites), Ukraine (four), Slovakia (two), Austria (one), Hungary (one) and Poland (one). Methods: Fine‐scale data on soil, topography, and vegetation structure as well as on bryophyte assemblages (taxonomic and functional composition, cover, species richness) were collected in 10‐m 2 plots. We used stratified random sampling to select six 10‐m 2 plots of traditionally managed grasslands in each of the 15 sites ( n  = 90). Climatic and landscape variables were extracted from online databases and available maps. Detailed data on present and historical land use were obtained from parcel owners. To assess the effect of drivers on bryophyte taxonomic and functional composition we applied canonical correspondence analysis (CCA) and redundancy analysis (RDA), respectively; for bryophyte species richness and bryophyte cover we used GLMMs. Forward stepwise variable selection procedure was used to find best set of drivers for each of the analyses. Results: Topographic (microrelief and solar radiation) and soil‐related factors (cover of stones and rocks, soil depth, moisture), as well as the cover of the herb layer and bare soil were the strongest drivers of bryophyte taxonomic composition. Among the management‐ and landscape‐related variables only mean size of grassland parcels within 1‐km 2 plot surroundings and grazing by horse were included in the CCA model explaining in total 25.9% of variation in species composition. Bryophyte functional composition was explained by a similar set of variables (RDA explained 27.3% of variation in functional composition) including additionally cover of gravel and burning. Solar radiation (negative effect) and management stability (positive effect) were the strongest drivers of bryophyte cover. Management stability had the strongest effect (positive) on bryophyte species richness, followed by grassland age (negative) and microrelief (positive). Conclusions: Taxonomic and functional composition of bryophyte assemblages as well as bryophyte cover in traditional grasslands were determined mainly by variables related to moisture and light availability. Management‐related factors seem to be at least as equally important as abiotic factors for bryophyte species richness and cover. Our results suggest that for maintaining bryophyte‐rich grasslands one should also consider stability of grassland management, that is, temporal continuity and regularity of management practices applied. Abstract : We studied environmental drivers of bryophyte assemblages in low‐intensity traditional grasslands of the Carpathians. Taxonomic and functional composition as well as bryophyte cover were determined mainly by variables related to moisture and light. Management‐related factors were equally important as abiotic factors for species richness and cover. For maintaining bryophyte‐rich grasslands temporal continuity and regularity of management practices applied is necessary.